2020
DOI: 10.7554/elife.60246
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline has distinct apicoplast-specific mechanisms of antimalarial activity

Abstract: Doxycycline (DOX) is a key antimalarial drug thought to kill Plasmodium parasites by blocking protein translation in the essential apicoplast organelle. Clinical use is primarily limited to prophylaxis due to delayed second-cycle parasite death at 1-3 µM serum concentrations. DOX concentrations >5 µM kill parasites with first-cycle activity but have been ascribed to off-target mechanisms outside the apicoplast. We report that 10 µM DOX blocks apicoplast biogenesis in the first cycle and is rescued by isopen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…This reciprocal dependence between organelle maintenance and metabolic outputs may extend to other apicoplast pathways in mosquito-and liver-stage P. falciparum as well as Toxoplasma gondii, where additional apicoplast outputs, such as fatty acids, contribute to parasite fitness and may support apicoplast maintenance. 4,5,[66][67][68] Our results also support the emerging paradigm 12,[16][17][18] that inhibition of apicoplast maintenance pathways can kill parasites with first-cycle kinetics that defy the delayed-death phenotype commonly observed for translation-blocking antibiotics such as doxycycline that target organelle housekeeping. 6,12 Indeed, blocking IPP synthesis causes same-cycle defects in apicoplast biogenesis, which are expected to produce non-viable parasite progeny independent of lethal dysfunctions in isoprenoid-dependent metabolism outside the organelle.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This reciprocal dependence between organelle maintenance and metabolic outputs may extend to other apicoplast pathways in mosquito-and liver-stage P. falciparum as well as Toxoplasma gondii, where additional apicoplast outputs, such as fatty acids, contribute to parasite fitness and may support apicoplast maintenance. 4,5,[66][67][68] Our results also support the emerging paradigm 12,[16][17][18] that inhibition of apicoplast maintenance pathways can kill parasites with first-cycle kinetics that defy the delayed-death phenotype commonly observed for translation-blocking antibiotics such as doxycycline that target organelle housekeeping. 6,12 Indeed, blocking IPP synthesis causes same-cycle defects in apicoplast biogenesis, which are expected to produce non-viable parasite progeny independent of lethal dysfunctions in isoprenoid-dependent metabolism outside the organelle.…”
Section: Discussionsupporting
confidence: 74%
“…These contrasting kinetics have led to a prevailing view in the literature that essential apicoplast functions can be segregated into two general categories: (1) anabolic pathways that produce metabolites required outside the apicoplast and whose inhibition causes first-cycle parasite death and (2) housekeeping pathways that are only required for organelle maintenance and whose inhibition causes delayed, second-cycle defects ( Ramya et al, 2007 ; Kennedy et al, 2019b ; Kennedy et al, 2019a ). Although this simple paradigm has been useful for conceptualizing general apicoplast functions, exceptions to this model have been reported ( Uddin et al, 2018 ; Amberg-Johnson et al, 2017 ; Boucher and Yeh, 2019 ; Okada et al, 2020 ) and thus its general validity remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also support the emerging paradigm 12,[16][17][18] that inhibition of apicoplast maintenance pathways can kill parasites with first-cycle kinetics that defy the delayed-death phenotype commonly observed for translation-blocking antibiotics such as doxycycline that target organelle housekeeping. 6,12 Indeed, blocking IPP synthesis causes same-cycle defects in apicoplast biogenesis, which are expected to produce non-viable parasite progeny independent of lethal dysfunctions in isoprenoid-dependent metabolism outside the organelle.…”
Section: Discussionsupporting
confidence: 77%
“…These contrasting kinetics have led to a prevailing view in the literature that essential apicoplast functions can be segregated into two general categories: (1) anabolic pathways that produce metabolites required outside the apicoplast and whose inhibition causes first-cycle parasite death or (2) housekeeping pathways that are only required for organelle maintenance and whose inhibition causes delayed, second-cycle defects. [13][14][15] Although this simple paradigm has been useful for conceptualizing general apicoplast functions, exceptions to this model have been reported 12,[16][17][18] and thus its general validity remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial action of tetracyclines is translation inhibition of the chromosomal genes by the drug binding to several proteins in the 30S ribosomal small subunit and to some different ribonucleic acids in the 16S rRNA (Gaillard et al, 2015). Multiple studies reported that the component of expression machinery for the genes contained in the genome of apicoplast, a unique plastid organelle of apicomplexan parasites, was the target of tetracyclines, and doxycycline directly inhibited the expression of genes in the apicoplast genome of P. falciparum (Dahl et al, 2006;Dahl and Rosenthal, 2007a;Chakraborty, 2016;Okada et al, 2020). Loss of apicoplast functions in the doxycycline-treated parasite led to delayed death in the second cycle (Dahl et al, 2006;Dahl and Rosenthal, 2007a).…”
Section: Tetracyclinesmentioning
confidence: 99%